تحديد العوامل المؤثرة في الطلب على السكن في سورية باستخدام الانحدار متعدد المتغيرات - بشماني, شكيب; أبو كف, براءة (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The research aims to specification of the important influencing economic and demographic in the request on the housing, that across Multivariate Regression technician. And that running from hypothesis of no significant effect for economic and demographic variables and in the request on the housing, and through the use of the descriptive analytic method and dependency on statements of timed series extended between years 1990 – 2010. The research founds that there is significant effect for the economic and demographic variables in the request on the housing, and to clarity is that the economic variables was most apparent power on interpretation the request on the housing from the power which showed the demographic variables. Just as the searching reached also the total financing banker for the purposes the residential economic variable the more impact in the request on the housing, whereas that rate of wedding the demographic variable the more impact in the request on the housing. يهدف هذا البحث إلى تحديد أهم المؤثرات الاقتصادية والديموغرافية في الطلب على السكن وذلك عبر استخدام تقنية الانحدار المتعدد المتغيرات. وانطلاقاً من فرضية عدم وجود تأثير ذو دلالة إحصائية للمتغيرات الاقتصادية والديموغرافية في الطلب على السكن, وباستخدام المنهج الوصفي التحليلي, واعتماداً على بيانات سلسلة زمنية ممتدة بين عامي 1990 – 2010. توصل البحث إلى وجود تأثير ذو دلالة إحصائية للمتغيرات الاقتصادية والديموغرافية في الطلب على السكن, ولكن تبين أن المتغيرات الاقتصادية كانت أكثر قدرة على تفسير ظاهرة الطلب على السكن من القدرة التي أبدتها المتغيرات الديموغرافية. كما توصل البحث أيضاً إلى أن إجمالي التمويل المصرفي للأغراض السكنية المتغير الاقتصادي الأكثر تأثير في الطلب على الإسكان, في حين أن معدل الزواج هو المتغير الديموغرافي الأكثر تأثير في الطلب على الإسكان.